Identifying changes in the drivers of ecosystem services: Socioeconomic changes underlie reduced provision of pollination service - Joaquim Bergamo, Pedro [UNESP]; F. Rito, Kátia; Agostini, Kayna; Deodato da Silva e Silva, Felipe; M. Maués, Márcia; R. Rech, André; A. Garibaldi, Lucas; Nic Lughadha, Eimear; M. Saraiva, Antonio; Y. Tsukahara, Rodrigo; F. Viana, Blandina; Casas, Grasiela; et al. (Elsevier, 2025)
The impact of land use changes on ecosystem services (ES) or Nature's Contributions to People (NCP) is relatively well-known, but the influence of socioeconomic changes on ES remains less clear, especially at larger spatial scales. Multiple socioeconomic factors influence the demand for a service (i.e. higher economic income and human development can increase demand for ES) and the provision of such service (i.e. environmental policies and cultural relationships with nature may enhance access to ES). Such complex relationships require a multidimensional approach to understand the socioeconomic drivers of change of ES. We investigated how socioeconomic drivers affect demand, diversity and provision of crop pollination service. Our Brazil-wide assessment spans a decade (2006-17) and encompasses a period of rapid land use intensification and concentration of land ownership. Our results revealed that the replacement of small and diverse pollinator-dependent farming systems by large pollinator-dependent monocultures has led to deficits in crop pollination services, with demand increasing by 3.3% while diversity and provision have decreased by 16.1 and 22.5%, respectively. These changes are linked to increased wealth concentration and social inequality, as regions that presented concentrated land ownership and limited access to credit were associated with reduced pollination provision. Our study provided a country-wide quantitative assessment of socioeconomic drivers of change in ES to reveal an association between social inequality and reduced ES provision.
Keywords: Agricultural production; Biodiversity valuation; Environmental management; Nature's contributions to people; Pollination service; Socio-ecological systems